Middle cerebral artery doppler and umbilical artery doppler as predictors Of perinatal outcome in small for gestational age fetuses in Hospital USM, Kubang Kerian, Kelantan - Mohd Jami, Amilia Afzan; Che Yaakob, Che Anuar (LAP Lambert Academic Publishing, 2014)
Small for gestational age babies are prone to get adverse perinatal outcome. They have increased risk of perinatal mortality, morbidity and neuro-developmental impairment.Doppler studies help to assess the condition of these babies in-utero, thus help to plan and ensure a better outcome of small fetuses. Monitoring and assessment provide a better collaboration between the pediatric team and the obstetric team. Such a collaboration help to reduce the neonatal intensive care unit stay and avoid delivery of severely premature fetuses without prior planning for post-delivery back up. It is hoped that the analysis of this study will help the obstetricians to decide and counsel patients on timing of delivery, and make necessary preparations before the delivery of these high risk fetuses.